Evaluating the Efficacy of Varying Concentrations of Metarhizium anisopliae Against Bactrocera cucurvitae Under In-Vitro Conditions - Salibo, Andal; Mendez, Dwight; Dicolano, Musa; Usop, Muslimin; Ebrahim, JN Mocktar; Atong, Jeanneflor; Dionaldo, Shiela Mae (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to evaluate the effectiveness of the entomopathogenic fungus Metarhizium anisopliae in controlling the cucurbit fruit fly (Bactrocera cucurbitae) under in-vitro conditions, addressing the need for sustainable alternatives to chemical pesticides. The research focused on developing eco-friendly pest management strategies to mitigate the economic losses caused by B. cucurbitae infestations in squash cultivation. A randomized complete block design (RCBD) was employed, testing five varying concentrations of M. anisopliae spore solution. Each treatment was replicated four times, using 20 fruit flies per replicate. The spore solutions were allocated for each treatment, and mortality rates, mummification times, and toxicity levels were recorded. Statistical analyses, including ANOVA and log-probit analysis, were used to determine lethal concentrations and times for effective control. The results demonstrated a clear dose-response relationship, with higher spore concentrations leading to significantly higher mortality rates and faster mummification times. A concentration of 6.0 × 10⁵ Colony-Forming Unit CFU/mL was necessary for substantial population suppression, with lethal concentrations for 50% and 99% mortality calculated as 2.65 × 10⁵ (CFU)/mL and 1.38 × 10⁵ CFU/mL, respectively. These findings suggest that M. anisopliae is an effective biological control agent against B. cucurbitae, offering a sustainable alternative to chemical pesticides. Further research is recommended to assess its efficacy in field applications and to evaluate potential long-term ecological impacts.